2018
DOI: 10.1089/biores.2018.0018
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Risk Among Women in Jail

Abstract: Over 200,000 women are diagnosed with breast cancer each year, and incarcerated women face unique risks associated with poor access to healthcare. Regular mammography can diagnose breast cancer early, giving the patient the best chance of survival. The objective of this study was to determine the proportion of jail incarcerated women who have received a mammogram and were up-to-date based on the most recent United States Preventive Services Task Force recommendations. This was a secondary analysis of data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
0
17
2
Order By: Relevance
“…We were encouraged to find that most of the older women in our study at some point in their lives accessed preventive health services, including mammograms (89.2%), Pap tests (98.7%), and, when necessary, follow-up visits for abnormal Pap tests (100%). Other studies with women in the CLS have reported lifetime mammogram rates of around 75%, with up-to-date screenings (i.e., within two years) closer to 40% (Pickett et al, 2018). Our findings related to Pap screenings may not be representative of all CLS-involved older adult women, since participants in one of the three cohorts (the Kansas City group) had participated in a previous interventional study to increase those rates.…”
Section: Discussionmentioning
confidence: 91%
“…We were encouraged to find that most of the older women in our study at some point in their lives accessed preventive health services, including mammograms (89.2%), Pap tests (98.7%), and, when necessary, follow-up visits for abnormal Pap tests (100%). Other studies with women in the CLS have reported lifetime mammogram rates of around 75%, with up-to-date screenings (i.e., within two years) closer to 40% (Pickett et al, 2018). Our findings related to Pap screenings may not be representative of all CLS-involved older adult women, since participants in one of the three cohorts (the Kansas City group) had participated in a previous interventional study to increase those rates.…”
Section: Discussionmentioning
confidence: 91%
“…Compared with the general population, rates of breast and cervical cancer are higher among incarcerated women, likely related to underscreening before incarceration and while in custody. 16,17 Follow-up of abnormal Papanicolaou test or mammogram findings can also present challenges for incarcerated female patients, particularly in short-stay facilities because women may be released before results are returned. In these cases, tracking systems and contact with community health care professionals may be a potential solution to facilitate postrelease cancer prevention and diagnosis.…”
Section: The Burden Of Cancer In the Us Correctional Systemmentioning
confidence: 99%
“…Even if escalated for medical review, incarcerated individuals may still face several challenges in obtaining an evaluation by a qualified health care professional including long waiting lists and requirement for co-pays. 17,18,20 Alternatively, prisons are facilities designated for long-term incarceration (typically >1 year sentence) and the oversight and management of access to care within these facilities is governed at the state and/or federal level providing more central standardization to the working operations. Before 1976, the only medical care offered in 65% of US jails was first aid.…”
Section: The Burden Of Cancer In the Us Correctional Systemmentioning
confidence: 99%
“…Women with criminal justice histories have increased risk for many sexual health-related problems such as increased prevalence of sexually transmitted infections (STIs), high rates of unintended pregnancy, cervical cancer, and low rates of up-to-date cervical and breast cancer screening (Javanbakht et al , 2014; Wiehe et al , 2015; Ramaswamy et al , 2017; Pickett et al , 2018; Binswanger et al , 2009; Clarke et al , 2006). As women transition back into the community, they are confronted with a host of competing priorities like seeking stable housing, reconnecting with children, reinstating state assistance, finding employment and meeting other probation and parole requirements (Peabody et al , 2014; Freudenberg et al , 2008).…”
Section: Introductionmentioning
confidence: 99%